An investigation on systematic history and distribution areas of tarek (Alburnus tarichi (Güldenstädt, 1814)) - Atici, A. A.; Elp, M.; Sen, F. (FapUNIFESP (SciELO), 2021)
Abstract This study aimed to determine the distribution area of tarek (Alburnus tarichi (Güldenstädt, 1814)) and to define how it must be called according to the scientific name by evaluating its previous studies made by various systematisers and their reports on its distribution, and by comparing literature knowledge. The taxonomic characteristics of the collected samples were evaluated and several measurements and counts were taken on the samples; analfin origin 0-4 scales behind dorsal fin-base; 72-91 lateral line scales; 21-29 gill rakers; 7½-10 branched dorsal-fin rays and 10-12½ branched anal-fin rays. Body and caudal peduncle was moderately compressed. Body was covered by overlapping scales. Tarek has five different populations in the Basin. They are Van, Erçek, Nazik and Aygır Lakes and Koçköprü Dam Lake populations. The main living area of the tarek population is Lake Van; however, between May and June, mature individuals of tarek enter to tributaries of Van Lake. Some of them are Karasu, Bendimahi, Deliçay, Zilan, Karmuç, Sapur, Yanıkçay, Gevaş, Engil, Kurubaş and Akköprü Streams. At the end of study, it was concluded that tarek should be called as Alburnus tarichi (Güldenstädt, 1814) and it is an endemic fish species distributed only in Van Lake Basin.
Keywords: Gills; Bacia do Lago Van; QH301-705.5; Science; Q; Botany; Cyprinidae; taxonomia; Van Lake Basin; taxonomy; Lakes; QL1-991; Rivers; QK1-989; Animals; Humans; Biology (General); Zoology; Chalcalburnus tarichi; Alburnus tarichi; 6. Clean water; 14. Life underwater